ISSUES OF PRIVILEGES AND IMMUNITIES OF INTERNATIONAL ORGANIZATIONS AND THEIR OFFICIALS IN INTERNATIONAL LAW (TSUL LEGAL REPORT, 2026)
The theory that individuals are legally equal before the law and the laws of society has been developed for a long time. Although these ideas and principles are still evolving, sometimes individuals such as international organizations and their officials are granted “additional” immunity and other facilities. This article analyzes the existing immunities and privileges in international organizations and their officials, the legal framework and the application of immunity theories of international law in particular international organizations.